2005
DOI: 10.1203/01.pdr.0000149108.44152.d3
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Exposure Impairs Alveolar Macrophage Function via Decreased Glutathione Availability

Abstract: Immature function of the alveolar macrophage increases the risk of pulmonary infections in premature newborns. In utero alcohol increases fetal systemic oxidative stress. Because the premature lung is deficient in glutathione (GSH), we hypothesized that chronic in utero alcohol (ethanol) exposure exacerbates the oxidative stress within the developing lung, thereby impairing alveolar macrophage function. Additionally, we evaluated the effects of in vivo and in vitro GSH availability on ethanol-exposed macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 51 publications
4
72
0
Order By: Relevance
“…Maternal alcohol consumption during pregnancy and its effects on fetal immunity remains a largely unexplored area of clinical significance. Several studies have already demonstrated that newborns exposed to ethanol during prenatal life have a higher incidence of infection (Gauthier et al, 2004;Gauthier et al, 2005b). The exact mechanism by which this occurs is not fully understood but it is possible that reduction in tracheal CBF and SP-A may increase susceptibility to infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal alcohol consumption during pregnancy and its effects on fetal immunity remains a largely unexplored area of clinical significance. Several studies have already demonstrated that newborns exposed to ethanol during prenatal life have a higher incidence of infection (Gauthier et al, 2004;Gauthier et al, 2005b). The exact mechanism by which this occurs is not fully understood but it is possible that reduction in tracheal CBF and SP-A may increase susceptibility to infections.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which this occurs is not fully understood but it is possible that reduction in tracheal CBF and SP-A may increase susceptibility to infections. Ethanol consumption has been shown to have a suppressive effect on cellular components of the innate immune system such as macrophages (Gauthier et al, 2005b) and/or neutrophils (Vinson et al, 1998), all of which may occur concurrently with reductions in CBF and SPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alveolar macrophages were fixed with 3.7% paraformaldehyde, and nonspecific binding was blocked with bovine serum albumin. Apoptosis was determined by staining for the cleaved moiety of the DNA repair enzyme poly(ADP-ribose) polymerase (PARP), an indicator of the apoptosis pathway (10,17). The primary antibody for cleaved PARP (Oncogene, Cambridge, MA) was added in a 1:100 dilution, and the sample was incubated for 2 h. Cells were serially rinsed with phosphate-buffered saline, and the secondary antibody (anti-rabbit IgG; AlexaFluor) was added in a 1:200 dilution for 1 h. Apoptosis was also evaluated after staining with the ApopTag Plus kit (Oncor, Gaithersburg, MD), which stains TdT-mediated dUTP nick end labeling (TUNEL)-positive cells.…”
Section: Rat Model Of Chronic Ethanol Ingestionmentioning
confidence: 99%
“…The process involves immune cells, proliferation of remaining epithelial cells, and recruitment of different progenitor populations. Prior research shows that fetal alcohol exposure or vitamin C deficiency affects lung cell populations and function in postnatal life (15)(16)(17), implying that the character of the scaffold influences regeneration. Systematic knowledge of exposure memory (3,18) is needed to determine whether conditioning to reverse exposure memory will promote lung regeneration.…”
mentioning
confidence: 99%